Open Source Systems c - Damiani, Ernesto; Fitzgerald, Brian; Scacchi, Walt.; Scotto, Marco; Succi, Giancarlo; SpringerLink (Online service) (Boston, MA : Springer US, 2006)
International Federation for Information Processing The IFIP series publishes state-of-the-art results in the sciences and technologies of information and communication. The scope of the series includes: foundations of computer science; software theory and practice; education; computer applications in technology; communication systems; systems modeling and optimization; information systems; computers and society; computer systems technology; security and protection in information processing systems; artificial intelligence; and human-computer interaction. Proceedings and post-proceedings of referred international conferences in computer science and interdisciplinary fields are featured. These results often precede journal publication and represent the most current research. The principal aim of the IFIP series is to encourage education and the dissemination and exchange of information about all aspects of computing. For more information about the 300 other books in the IFIP series, please visit www.springer.com. For more information about IFIP, please visit www.ifip.org.
Foundations and Rationale of Open Source software -- On the Weickian Model in the Context of Open Source Software Development: Some Preliminary Insights -- Conceptual Modelling as a New Entry in the Bazaar: The Open Model Approach -- Evolution of Open Source Communities -- Tools and Infrastructures for OSS development -- Retrieving Open Source Software Licenses -- Beyond Low-Hanging Fruit: Seeking the Next Generation in FLOSS Data Mining -- Call for Quality: Open Source Software Quality Observation -- Knowledge Management in OSS -- Towards an Ontology for Open Source Software Development -- From Individual Contribution to Group Learning -- The role of mental models in FLOSS development work practices -- A Robust Open Source Exchange for Open Source Software Development -- of OSS in Companies and PAs -- The Organizational Adoption of Open Source Server Software by Belgian Organizations -- The Introduction of OpenOffice.org in the Brussels Public Administration -- Networks of Open Source Health Care Action -- Licensing Services: An (3z(BOpen(3y (BPerspective -- Perceptions and Uptake of Open Source in Swedish Organisations -- A study on the introduction of Open Source Software in the Public Administration -- Exploring the potential of OSS in Air Traffic Management -- Empirical Analysis of OSS -- Institutional Entrepreneurs and the Bricolage of Intellectual Property Discourses -- Life cycle of Defects in Open Source Software Projects -- Insiders and outsiders: paid contributors and the dynamics of cooperation in community led F/OS projects -- Adopting Open Source for Mission-Critical Applications: A Case Study on Single Sign-On -- Participation in Free and Open Source Communities: An Empirical Study of Community Members$1 (BPerceptions -- Collaborative Maintenance in Large Open-Source Projects -- Case Studies and Experiments -- Comparing macro development for personal productivity tools: an experience in validating accessibility of Talking Books -- A tool to support the introduction of GNU/Linux desktop system in a professional environment -- A Framework for Teaching Software Testing using F/OSS Methodology -- Organization of Internet Standards -- Contributor Turnover in Libre Software Projects -- Critical Success Factors for Migrating to OSS-on-the-Desktop: Common Themes across Three South African Case Studies -- Impact of OSS on Social Networks -- Communication Networks in an Open Source Software Project -- Impact of Social Ties on Open Source Project Team Formation -- Social dynamics of free and open source team communications -- Posters -- How is it possible to profit from innovation in the absence of any appropriability? -- Producing and Interpreting Debug Texts -- A graphical installation system for the GNU/Linux Debian distribution -- The micro-dynamics of open source software development activity -- Development Platforms as a Niche for Software Companies in Open Source Software -- Reusable Parser Generation from Open Source Compilers -- Open Source Software Development (OSSD) Based On Software Engineering -- Open Source in Web-based Periodicals -- Software Patents and Open Source Software in the European Union: Evidences of a Trade-Off?.s
Keywords: Computer science; Software engineering; Operating systems (Computers).; Application software; Computer Science; Software Engineering/Programming and Operating Systems; Computer Applications; Operating Systems; Software Engineering; Electronic books